2014
DOI: 10.1038/onc.2014.214
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-25 promotes gastric cancer migration, invasion and proliferation by directly targeting transducer of ERBB2, 1 and correlates with poor survival

Abstract: Gastric cancer (GC) is one of the most common tumors and the molecular mechanism underlying its metastasis is still largely unclear. Here, we show that miR-25 was overexpressed in plasma and primary tumor tissues of GC patients with tumor node metastasis stage (III or IV) or lymph node metastasis. MiR-25 inhibition significantly decreased the metastasis, invasion and proliferation of GC cells in vitro, and reduced their capacity to develop distal pulmonary metastases and peritoneal dissemination in vivo. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 36 publications
3
95
0
Order By: Relevance
“…Down-regulation of NEFL could significantly attenuate the inhibitory effects of knockdown miR-25 on the proliferation, migration, and invasion of U251 cells via activation of the mTOR pathway. LATS2 and ERBB2 were also the direct targets of miR-25 [17,18,34]. LATS2 is a tumor suppressor gene of gastric adenocarcinoma (GAC) [34], malignant mesothelioma [35], ovarian cancer [18], breast cancer [36], non-small cell lung cancer [37], and prostate cancer [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Down-regulation of NEFL could significantly attenuate the inhibitory effects of knockdown miR-25 on the proliferation, migration, and invasion of U251 cells via activation of the mTOR pathway. LATS2 and ERBB2 were also the direct targets of miR-25 [17,18,34]. LATS2 is a tumor suppressor gene of gastric adenocarcinoma (GAC) [34], malignant mesothelioma [35], ovarian cancer [18], breast cancer [36], non-small cell lung cancer [37], and prostate cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their small size and influence in a broad range of biological processes, miRNAs are very attractive therapeutic targets for GBM. miR-25 is one of the most overexpressed miRNAs in a number of profiling experiments designed for the detection of miRNAs dysregulated in human cancers [16][17][18][19][20][21][22][23][24][25]29]. Li et al reported that miR-25 promoted gastric cancer migration, invasion, and proliferation by directly targeting transducer of ERBB2 and 1 and correlated with poor survival [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have demonstrated that miRNAs are associated with tumour development and progression (83,84). Certain miRNAs have been established to be associated with peritoneal dissemination in gastric cancer (85)(86)(87). Zheng et al (85) reported that microRNA (miR)-409-3p inhibited the ability of gastric cancer cells to invade and metastasise via targeting radixin.…”
Section: Involvement Of Microrna In Peritoneal Disseminationmentioning
confidence: 99%
“…Another previous study demonstrated that miR-495 and miR-551a suppressed gastric cancer cell migration and invasion by targeting PRL-3, which exhibits significantly increased expression levels in primary gastric cancer cells with peritoneal dissemination (86). miR-25 was identified to enhance gastric cancer progression by targeting Erb-B2 receptor tyrosine kinase 2 both in vitro and in vivo (87). Other miRNAs have been reported to correlate with peritoneal dissemination in gastric cancer, including miR-200b (88), miR-125a-3q (89) and let-7 miRNAs (90).…”
Section: Involvement Of Microrna In Peritoneal Disseminationmentioning
confidence: 99%